1989
DOI: 10.1128/iai.57.4.1025-1029.1989
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of penicillin G-resistant Neisseria meningitidis from Spain

Abstract: Genotypic and phenotypic diversity among 16 penicillin G-resistant (Penr) isolates of Neisseria meningitidis recovered from human blood or cerebrospinal fluid in Spain was compared with that among 12 penicillinsusceptible (Pens) isolates by the use of multilocus enzyme electrophoresis, serotyping, auxotroph testing in chemically defined media, and sodium dodecyl sulfate-polyacrylamide gel electrophoresis of penicillin-binding proteins (PBPs). Thirteen distinctive multilocus enzyme genotypes (electrophoretic ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
4
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 17 publications
2
4
0
Order By: Relevance
“…In the present study, 13 such strains were found, none of which produced beta-lactamase with the nitrocefin disk. As observed by others (5,19), these strains do not seem to arise from a single clone. Effectively, apart from the three strains related to the outbreak described by Perron and Laferrière (25), the strains belonged to serogroup B, C, or Y and had different serotypes, subtypes, and ET profiles.…”
Section: Discussionsupporting
confidence: 67%
“…In the present study, 13 such strains were found, none of which produced beta-lactamase with the nitrocefin disk. As observed by others (5,19), these strains do not seem to arise from a single clone. Effectively, apart from the three strains related to the outbreak described by Perron and Laferrière (25), the strains belonged to serogroup B, C, or Y and had different serotypes, subtypes, and ET profiles.…”
Section: Discussionsupporting
confidence: 67%
“…Rather, this pattern supports the notion that most pathogenic bacteria within a species are composed of a limited number of clones and the genetic diversity observed is restricted to single isolates. Four resistant strains in lineage A (ETs 6, 7, 21, and 22) and all of those in lineages B and C were single representatives of distinct ETs in agreement with their individual PBP properties, confirming (15). One of the surprising results was that six ETs were represented by isolates of two or more different capsular types, the most inhomogeneous groups of strains being those represented in ET 5a and b.…”
supporting
confidence: 64%
“…One study found that group B serotype\subtype 4 : P1.15 was associated with 51n4 % of penicillin resistance and group C and non-serogroupable serotype type 2b were associated with 86 % and 87 % of penicillin resistance respectively [22]. However, an examination of 16 penicillin G-resistant strains in Spain failed to find a serotype specific association for penicillin resistant isolates [34]. We found that serogroups\types\subtypes B : 4 : P.14, B : NT : P1.9, B : NT : P1.16, C:2a : P1.2 and C : 2a : P1.5 were associated with a higher proportion of resistance as well as disease.…”
Section: Discussionmentioning
confidence: 99%